Benefits of smoking cessation for coronary heart disease patients - Adi Hidayat (Faculty of Medicine, Universitas Trisakti, 2015)
Cardiovascular disease (CVD) incidence increases with age and is frequently higher in the elderly.(1) Therefore prevention of CVD in the elderly through management of risk factors is important in order to reduce the risk of coronary heart disease (CHD). There are several risk factors of CVD that can be modified, such as smoking, physical activity, and unhealthy diet. Cessation of smoking is the most potent measure to prevent thousands of CVD events and death